2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037320
|View full text |Cite
|
Sign up to set email alerts
|

Higuchi fractal dimension of the electroencephalogram as a biomarker for early detection of Alzheimer's disease

Abstract: It is widely accepted that early diagnosis of Alzheimer's disease (AD) makes it possible for patients to gain access to appropriate health care services and would facilitate the development of new therapies. AD starts many years before its clinical manifestations and a biomarker that provides a measure of changes in the brain in this period would be useful for early diagnosis of AD. Given the rapid increase in the number of older people suffering from AD, there is a need for an accurate, low-cost and easy to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 29 publications
4
32
0
Order By: Relevance
“…In this case, the results show that HFD values for AD patients are lower than those for normal subjects. This result is consistent with the finding in other studies [46,80]. As with the TsEn, the differences between HFD biomarkers for AD patients and normal subjects for the EEG frequency bands (i.e., delta, theta, and alpha bands) were Fp1 Fp2 F7 F3 FZ F4 F8 T3 C3 CZ C4 T4 T5 P3 PZ P4 T6 O1 O2 EEG channel Whole EEG …”
Section: Resultsupporting
confidence: 81%
See 3 more Smart Citations
“…In this case, the results show that HFD values for AD patients are lower than those for normal subjects. This result is consistent with the finding in other studies [46,80]. As with the TsEn, the differences between HFD biomarkers for AD patients and normal subjects for the EEG frequency bands (i.e., delta, theta, and alpha bands) were Fp1 Fp2 F7 F3 FZ F4 F8 T3 C3 CZ C4 T4 T5 P3 PZ P4 T6 O1 O2 EEG channel Whole EEG …”
Section: Resultsupporting
confidence: 81%
“…In addition, HFD provides a more accurate measure of the complexity of signals compared to other methods [75,78,79] and it has been shown to be an efficient method for discriminating between AD patients and normal subjects [31,80]. HFD of the EEG is potentially a good biomarker of AD diagnosis as it is significantly lower in AD patients than in normal subjects [46,80,81]. Smits et al found that HFD is sensitive to neural changes selectively related to AD patients and normal subjects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the complexity in the EEG signals in patients with AD, some studies have investigated an approach focusing on deterministic chaos and fractal dimension such as correlation dimension and Lyapunov exponent (24). These studies reported reduced complexity in the neural activity of patients with AD (8,(25)(26)(27)(28)(29)(30). While, EEG dynamics plays a different role at each temporal-scale, such as memory function, cognitive function, and perceptual function in the theta, beta, and gamma bands, respectively (31).…”
Section: Introductionmentioning
confidence: 99%